2009
DOI: 10.1007/s00468-009-0400-6
|View full text |Cite
|
Sign up to set email alerts
|

Variation in photoinhibition among Sasa senanensis, Quercus mongolica, and Acer mono in the understory of a deciduous broad-leaved forest exposed to canopy gaps caused by typhoons

Abstract: To elucidate mechanisms for tolerating sudden increases in light intensity following canopy gap formation, we investigated susceptibility to photoinhibition in the evergreen clonal plant bamboo, Sasa senanensis, and two deciduous broadleaf woody plants, Quercus mongolica, and Acer mono. We measured pre-dawn photochemical efficiency of photosystem II (F v /F m ) in plants exposed to canopy gaps and in shade-grown plants through the month following gap formation. Photoinhibition (indicated by decreased F v /F m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 57 publications
(84 reference statements)
3
9
0
1
Order By: Relevance
“…F v /F m , the primary target of photoinhibitory processes (Hussner et al, 2010), has been shown to be a reliable indicator of PSII activity Dias & Marenco, 2006;Hussner et al, 2010;Tobita et al, 2010). As in previous studies (Dias & Marenco, 2006;Kitao et al, 2000;Naramoto et al, 2006;Tobita et al, 2010;Valladares et al, 2002;Yamashita et al, 2000), we found that when shade-developed leaves were exposed to high light, F v /F m decreased at the first measurement and subsequently recovered gradually, indicating photoinhibition and recovery of photoinhibition. The decline of F v /F m can happen after a very short time of exposure (Dias & Marenco, 2006).…”
Section: Chlorophyll Fluorescencesupporting
confidence: 86%
See 1 more Smart Citation
“…F v /F m , the primary target of photoinhibitory processes (Hussner et al, 2010), has been shown to be a reliable indicator of PSII activity Dias & Marenco, 2006;Hussner et al, 2010;Tobita et al, 2010). As in previous studies (Dias & Marenco, 2006;Kitao et al, 2000;Naramoto et al, 2006;Tobita et al, 2010;Valladares et al, 2002;Yamashita et al, 2000), we found that when shade-developed leaves were exposed to high light, F v /F m decreased at the first measurement and subsequently recovered gradually, indicating photoinhibition and recovery of photoinhibition. The decline of F v /F m can happen after a very short time of exposure (Dias & Marenco, 2006).…”
Section: Chlorophyll Fluorescencesupporting
confidence: 86%
“…A number of investigations have been conducted to examine plant morphological and physiological responses to variations in illumination (Gatti et al, 2011;Guo et al, 2013;Naramoto et al, 2006;Saldaňa-Acosta et al, 2009;Tobita et al, 2010;Valladares et al, 2002;Yamashita et al, 2000). In some of these studies, plants were subjected to low light illumination for some time and then were transferred to high light condition.…”
Section: Introductionmentioning
confidence: 99%
“…Higher SLA values can lead to higher absorption efficiency under shade (Sanches and Válio 2006), but when these thinner leaves are suddenly exposed to full sunlight, photoinhibition could be exacerbated. Similar findings were found by Tobita et al (2010), where the leaves of Sasa senanensis with higher LMA (the opposite of SLA) were less susceptible to photoinhibition after increases in irradiance than that of Quercus mongolica and Acer mono. Although C. sceptrum lost its leaves shortly after its transfer, new leaves were produced under full sunlight.…”
Section: Cuspidaria Spectrumsupporting
confidence: 83%
“…During leaf maturation of Japanese oak, LMA reaches its maximum, accompanied with an increase in net photosynthetic rate, several weeks after the leaves are fully expanded and the light environment within a canopy is fixed (Tobita unpublished data 37 ). Although the sun/shade anatomy of deciduous leaves is mainly determined by the light condition in the previous year 38 , less extent but some plasticity exists in leaf morphological change in response to current-year light environment 39 . For Japanese oak, LMA and net photosynthetic rate increased during June, after the leaf expansion had completed at the end of May (Tobita unpublished data).…”
Section: Discussionmentioning
confidence: 99%